Assessment of Science Production in the field of pediatric surgery in Iran, Turkey, India and Pakistan - Nasibeh Khaleghnejad Tabari; Ahmad Khaleghnejad Tabari (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: Scientific progress is one of the main parts of development in any country. One of the means of assessing it is the number of scientific papers which are published in internationally approved journals. In this article we will compare scientific production in the field of pediatric surgery between Iran and three other Asian countries: Turkey, India and Pakistan during 25 years. Material and methods: Using scientometric methods we analyzed scientific productions in the field of pediatric surgery indexed in bibliographic databases such as PubMed and Scopus during 25 years from 1990-2015 by 4 Asian countries: Iran, Turkey, India and Pakistan. Results: Turkey had the most articles indexed in ISI web of Science with 843 articles, India had 545 articles, Iran had 127 articles and Pakistan had 29 articles in 25 years. Conclusion: Our main intention was to assess the research activity of pediatric surgeons in Iran. And what we found showed that despite similarity in the population and budget among neighboring countries our scientific production is lower.